2021
DOI: 10.1108/bfj-05-2021-0524
|View full text |Cite
|
Sign up to set email alerts
|

Effect of banana peel flour on rheological, physico-chemical, mineral content and sensory properties of chicken patties

Abstract: PurposeThe present study was conducted to evaluate the effect of banana peel flour as fat replacer on rheological, physico-chemical, textural, mineral content and sensory properties of chicken patties.Design/methodology/approachUltra low fat chicken patties were prepared with incorporation of banana peel flour at 0% (C), 1% (BP1), 2% (BP2) and 3% (BP3) levels separately to replace 50% externally added vegetable fat in formulation and evaluated for various quality characteristics and sensory attributes.Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…The taste was perceived as less in the control sample due to the presence of starch which provides a blunt flavor and hard texture. The scoring of sensory evaluation agrees with the findings of Chappalwar et al (2021) and Zaini, Sintang & Pindi (2020b) who reported similar effects of banana peel powder and flour on organoleptic characteristics of chicken patties. Contradictory results were reported by another research performed by Zaini, Sintang & Pindi (2020b) in which banana peel powder was used to improve the sensorial characteristics of chicken sausages but results depicted that addition of banana peel powder in concentrations of >2% decreased the organoleptic perception of sausage samples.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The taste was perceived as less in the control sample due to the presence of starch which provides a blunt flavor and hard texture. The scoring of sensory evaluation agrees with the findings of Chappalwar et al (2021) and Zaini, Sintang & Pindi (2020b) who reported similar effects of banana peel powder and flour on organoleptic characteristics of chicken patties. Contradictory results were reported by another research performed by Zaini, Sintang & Pindi (2020b) in which banana peel powder was used to improve the sensorial characteristics of chicken sausages but results depicted that addition of banana peel powder in concentrations of >2% decreased the organoleptic perception of sausage samples.…”
Section: Discussionsupporting
confidence: 88%
“…The ash content improved significantly for nuggets as banana peel powder is a rich source of minerals. Chappalwar et al (2021) prepared chicken patties by the incorporation of banana peel flour and observed a similar effect on the ash content of the product. In another study it was reported that banana peel powder was used to improve the fibre content of waffle cones and results depicted a significant increase in the fibre content of prepared sample ( Zanariah, Zaleqha & Lisnurjannah, 2019 ).…”
Section: Discussionmentioning
confidence: 79%
“…Addition of BPP results in an increase in the dietary fiber, water holding capacity and cooking yield of sausages with a decrease in their fat content (Mohd Zaini et al, 2022). Inclusion of BPP to develop very low‐fat chicken patties significantly increased moisture, ash content, and cooking yield along with the reduction in the emulsion stability, pH, water activity, fat, and cholesterol level compared to the control sample (Chappalwar et al, 2021). Additionally, chicken sausage incorporated with two different varieties of BP flours reported Saba BP flour to have poorer water, oil retention capacity and better swelling ability than Berangan BP flour.…”
Section: Applications Of Banana and Its By‐products In Food Industrymentioning
confidence: 99%